'Betweenness' and 'twofoldness': A cross-cultural interpretation of the aesthetic appreciation of paintings. Issue 2 (3rd April 2023) - Feng, Peng
ABSTRACT: In appreciating paintings, what we experience is either a result of their medium or object, regardless of whether the object is an actual thing, a fictional thing, an internal emotion, an abstract idea, or something else. However, the conceptions of 'betweenness' in traditional Chinese aesthetics and 'twofoldness' in contemporary Western aesthetics tell us that our experience of paintings might not be simply from the object or the medium itself but rather from a relation between the two. This study considers the intercultural value of the above concepts while examining how our aesthetic pleasure might derive from awareness of the object, the medium, and the play of our mind and body.